New interpretation of the boundary diffracted wave origin - Anokhov, S.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The important improvement for Young's model of diffraction is proposed. This interpretation is based on the statement about the existence of the energy transfer process directed from the remaining field towards the boundary wave, that is formally taken into account by introduction of a source for this wave on boundary of a geometrical shadow. The legitimacy of the application, in this case, of parabolic equation in the form of the standard equation of diffusion - thermal conductivity is validated. With the help of such approach it was obtained the compact analytical representation of this wave at the diffraction of a plane wave on a half-plane, which is completely concordant with Sommerfeld's rigorous solution and available experimental facts.